Polarization 3D imaging technology: a review - Li, Xuan; Liu, Zhiqiang; Cai, Yudong; Pan, Cunying; Song, Jiawei; Wang, Jinshou; Shao, Xiaopeng (Frontiers in Physics, 2023)
Polarization three-dimensional (3D) imaging technology has received extensive attention in recent years because of its advantages of high accuracy, long detection distance, simplicity, and low cost. The ambiguity in the normal obtained by the polarization characteristics of the target’s specular or diffuse reflected light limits the development of polarization 3D imaging technology. Over the past few decades, many shape from polarization techniques have been proposed to address the ambiguity issues, i.e., high-precision normal acquisition. Meanwhile, some polarization 3D imaging techniques attempt to extend experimental objects to complex specific targets and scenarios through a learning-based approach. Additionally, other problems and related solutions in polarization 3D imaging technology are also investigated. In this paper, the fundamental principles behind these technologies will be elucidated, experimental results will be presented to demonstrate the capabilities and limitations of these popular technologies, and finally, our perspectives on the remaining challenges of the polarization 3D imaging technology will be presented.